Drug and dye binding induced folding of the intrinsically disordered antimicrobial peptide CM15. Issue 65 (23rd August 2017) - Zsila, Ferenc; Bősze, Szilvia; Horváti, Kata; Szigyártó, Imola Cs.; Beke-Somfai, Tamás
Abstract : Drug binding induces the disorder-to-order conformational transition of the natively unfolded antimicrobial peptide CM15. Abstract : The rapid increase of antimicrobial resistance against conventional antibiotics has resulted in a significant focus on the use of peptides as antimicrobial agents. Understanding the structure and function relationships of these compounds is thus highly important, however, their in vivo actions are a complex issue, including interactions with small molecule agents. Here we report the folding inducing capability of some pharmaceutical substances and synthetic dyes on the intrinsically disordered (ID) cationic antimicrobial peptide CM15 (KWKLFKKIGAVLKVL). By employing circular dichroism (CD) spectroscopy, it is shown that some therapeutic drugs (suramin, pamoic acid, cromolyn) and polysulfonated dyes (Congo red, trypan blue) trigger the disorder-to-order conformational transition of CM15. The cooperative binding of 2–4 acidic molecules per peptide chain provokes its folding in a concentration dependent manner. Secondary structure analysis indicated the sharp and moderate rise of the α-helical and β-sheet content, respectively. According to semi-empirical quantum chemical calculations, these organic molecules may induce folding by forming multiple salt-bridges with lysine residues from both N- and C-terminals as well as from the middle of the CM15 sequence. Due to the mutual neutralization of the positive and negative charges, the water solubility of the resulting complexes decreases which favours their aggregation as detected by dynamic light scattering measurements. Our findings suggest that small molecules can dramatically affect the structure of antimicrobial peptides, which may potentially alter, either enhancing or attenuating, their efficiency. It is proposed that CM15 or similar ID peptides could be useful for preliminary screening of folding inducer effect of anionic drugs and biomolecules. The data presented herein may stimulate further studies on the structural and functional impacts of related compounds on ID peptides.